PENGARUH KONSENTRASI GARAM TERHADAP WARNA, TOTAL ASAM DAN TOTAL BAKTERI ASAM LAKTAT PIKEL UBI JALAR UNGU (Ipomoea batatas var Ayamurasaki) SELAMA FERMENTASI - Setiawan, Setiawan; Yuliana, Neti; Setyani, Sri (Jurnal Teknologi & Industri Hasil Pertanian, 2013)
The objective of this research was to investigate the influence of salt concentration during fermentation towards color stability of purple swee tpotato pickle. This experiment was arranged as a factorial design in completely randomized group design with two factors and three replications. The first factor was salt concentration (G) consisted of four levels: 3%, 6%, 9%, and 12%. The second factor was the fermentation duration (H) consisted of five levels; 0, 3, 6, 9, and 12 days. Data were analyzed using ANOVA further tested using polynomial orthogonal test at 1% and 5% level of significance. The results showed that the salt concentration and fermentation duration influenced total acid, pH and color stability. The best product was resulted from treatment of 3% salt concentration and 12 days fermentation duration with the characteristic as follows: total lactate acid bacteria (0.3 x 104 colony/mL), 1.6% total acid and the stable color score 4 (pink). Keywords: fermentation, pickle, purple sweet potato, salt